PENERAPAN AGAMA DALAM MODUL PSIKOSPIRITUAL DAN KESANNYA TERHADAP KESIHATAN SPIRITUAL: KAJIAN KES DI KOMPLEKS DAR ASSAADAH KUALA LUMPUR: The Application of Religion in Psychospiritual Modules and its Impact on Spiritual Health: A Case Study at Kompleks Dar Assaadah, Kuala Lumpur - Mohamad Jodi, Khairul Hamimah; Mohamad, Mohd Afifuddin; Che Seman, Azizi (Jurnal Syariah, 2014)
It is crucial to incorporate religious and psychospiritual health elements in the structured instrumentations modules used on the residents of rehab centres. Both elements can produce positive desired effects. The embedment of both elements can also contribute as a training and rehabilitation process for those who have previously involved in negative activities. This study attempts to examine the effectiveness of the psychospiritual modules on the residents of Kompleks Dar Assaadah (KDS) Kuala Lumpur during their stay at the centre. The research was based on the residents’ perspective towards the programme/modules they went through. Interviews and questionnaires were used to obtain the data. The study involved 33 residents of KDS, Kuala Lumpur, who have involved in a variety of offences. This study focused on the effectiveness of religious approaches applied on the residents and to what extent the said approaches influence their spiritual health, attitudes and morals, and also on their daily activities. The overall results show that religious-based modules/approaches are capable of producing positive impacts on the residents of KDS after they undergo the programmes.